2011
DOI: 10.1080/13032917.2011.556217
|View full text |Cite
|
Sign up to set email alerts
|

Exploring attitudes of Omani students towards vacations

Abstract: This study uses the theory of 'push' and 'pull' travel motivations to investigate holidaying attributes of Omani students studying at the Colleges of Applied Sciences, Ministry of Higher Education in Oman. The results indicate that the three most important push motivations for Omani students to travel abroad were 'to be mentally refreshed', followed by 'to learn something new or increase my knowledge', and 'to spend my time without worrying about my study'. The pull factors were such as 'safety and security at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Among the theoretical frameworks and models emanating during the evolvement process when researchers attempted to explain human motivation, the push-pull theory originally introduced by Dann (1977), is arguably the best-known and, is by now, commonly adopted in destination marketing research (Kim, Holland, & Han, 2013). The general appeal found by push-pull motivation theory among tourism researchers has been attributed to its intuitive approach (Klenosky, 2002) and simplicity (Mohsin & Alsawafi, 2011). The push-pull framework has been used extensively for studying why tourists travel (Chen & Chen, 2015;Li et al, 2013;Prayag & Hosany, 2014).…”
Section: Motivations Of Wine Touristsmentioning
confidence: 99%
“…Among the theoretical frameworks and models emanating during the evolvement process when researchers attempted to explain human motivation, the push-pull theory originally introduced by Dann (1977), is arguably the best-known and, is by now, commonly adopted in destination marketing research (Kim, Holland, & Han, 2013). The general appeal found by push-pull motivation theory among tourism researchers has been attributed to its intuitive approach (Klenosky, 2002) and simplicity (Mohsin & Alsawafi, 2011). The push-pull framework has been used extensively for studying why tourists travel (Chen & Chen, 2015;Li et al, 2013;Prayag & Hosany, 2014).…”
Section: Motivations Of Wine Touristsmentioning
confidence: 99%
“…All measures were assessed on a 7-point Likert Scale which ranged from 1 (of no importance) to 7 (extremely important). These measures have been frequently used in previous research (Mohsin & Ryan, 2007;Mohsin & Alsawafi, 2011).…”
Section: Development Of Measures and Questionnairementioning
confidence: 99%
“…These measures were adapted from the study done by Mohsin and Ryan (2007) and Mohsin and Alsawafi (2011). A 7-point Likert Scale was which ranged from 1 (of no attraction) to 7 (extremely attractive).…”
Section: Development Of Measures and Questionnairementioning
confidence: 99%
“…Previous studies also have attempted to examine differences across motivations by gender. Mohsin and Alsawafi (2011) also conclude that gender has a significant impact on some travel motivations. A female preference for shopping is highlighted in Xu et al's (2009) findings.…”
Section: Discussionmentioning
confidence: 81%
“…In the study of Kim et al (2007), knowledge, sports and adventure are indicated as significant motivational push factors for US students. In another study, some of the most significant push motivations for Omani students are 'to be mentally refreshed,' 'to learn something new or to increase knowledge' and 'to relax,' as stated by Mohsin and Alsawafi (2011). Escapism is a major motivation found in study by Thrane (2008).…”
Section: Discussionmentioning
confidence: 97%